2018
DOI: 10.1002/suco.201700289
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle reliability assessment of reinforced concrete beams shear‐strengthened with carbon fiber reinforced polymer strips in accordance with fib bulletin 14

Abstract: The results of time‐variant reliability analysis of shear‐strengthened reinforced concrete (RC) beams with externally bonded fiber‐reinforced polymer (FRP) are presented with an emphasis on the effects of environmental harshness and effective design parameters. The effects of chloride‐induced pitting corrosion and FRP degradation are considered using Monte Carlo simulation to assess the influence of environmental deterioration on the fib 2001 limit states instead of applying design reduction factors. For the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 56 publications
0
4
0
1
Order By: Relevance
“…performance. [2][3][4][5] It has been demonstrated that flexural behavior or shear performance of concrete beams improves dramatically by externally bonded FRP at their bottom sides or lateral faces. One of their most typical failure modes is interfacial failure between FRP and concrete of beams, and bonding performance of FRPconcrete interface is an important factor to determine the reinforcement effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…performance. [2][3][4][5] It has been demonstrated that flexural behavior or shear performance of concrete beams improves dramatically by externally bonded FRP at their bottom sides or lateral faces. One of their most typical failure modes is interfacial failure between FRP and concrete of beams, and bonding performance of FRPconcrete interface is an important factor to determine the reinforcement effect.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber‐reinforced polymer (FRP) has increasingly become a mainstream in the areas of retrofit and rehabilitation for concrete structures mainly thanks to its material advantages of high strength to weight ratios, superior corrosion resistance, greatly improving structural ductility and flexibly applying on various shapes of concrete members 1 . At present, most studies on reinforced concrete (RC) beams strengthened with FRP have focused on their static performance 2–5 . It has been demonstrated that flexural behavior or shear performance of concrete beams improves dramatically by externally bonded FRP at their bottom sides or lateral faces.…”
Section: Introductionmentioning
confidence: 99%
“…Guan et al found that brucite fiber could increase the strength and toughness of asphalt mixture. Meanwhile, the addition of fibers also can prevent the degradation of asphalt during transportation and construction [8][9][10]. C.Celauroet al [11] found the usability of basalt fibers in asphalt mixture has improved its resistance to permanent deformation.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, the using of carbon fiber reinforced polymer (CFRP) for strengthening and retrofitting of the existent structural member, and in enhancing the structural performance for the buildings during earthquakes considered to be a good solution in comparison to the other conventional strengthening methods like using steel. That attributed to the CFRP properties like its high strength, Low weight, ease of installation, corrosion resistance, flexibility to apply on any flat, curved, or geometrically irregular surfaces as well as its ability to improve the strength and ductility without adding stiffness to the elements . However, the premature failure resulted from the debonding of CFRP elements from concrete substrate prevents the CFRP from reaching its full strength.…”
Section: Introductionmentioning
confidence: 99%